High-entropy alloy oxide / nano silicon composite lithium ion battery negative electrode material and preparation method thereof

Through spinel structure and electrospinning technology of high-entropy alloy oxide and nano-silicon composite materials, the problem of insufficient specific capacity and cycle stability of the negative electrode material of lithium-ion batteries is solved, and the battery performance with high energy density and long life is achieved .

CN119181759AActive Publication Date: 2024-12-24GUANGXI UNIV FOR NATITIES
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411228368.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2024-12-24
Estimated Expiration
2044-09-03

AI Technical Summary

Technical Problem

The specific capacity and cycle stability of existing lithium-ion battery anode materials are difficult to meet the needs of high energy density and long life, especially in electric vehicle applications.

Method used

High-entropy alloy oxide/nanosilicon composite material is used to prepare spinel structure (FeCoNiCrMn)3O4/Si material through electrospinning technology, combining modified nanosilicon and transition metal alloy to form an oxide alloy shell wrapped in nanosilicon Core-shell structure to improve mechanical properties and cyclic stability.

Benefits of technology

It significantly improves the cyclic stability and specific capacity of the negative electrode material of lithium-ion battery, enhances mechanical properties and lithium-ion conductivity, and extends the service life of the electrode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005025350230000011
    Figure HDA0005025350230000011
  • Figure HDA0005025350230000012
    Figure HDA0005025350230000012
  • Figure HDA0005025350230000013
    Figure HDA0005025350230000013
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion battery negative electrode materials, and particularly relates to a high-entropy alloy oxide / nano silicon composite lithium ion battery negative electrode material and a preparation method thereof. The preparation method comprises the following steps: 1, preparing modified nano silicon, 2, preparing an electrostatic spinning solution, 3, weighing a proper amount of ferric salt, nickel salt, cobalt salt, chromium salt, manganese salt and the modified nano silicon, adding into a certain amount of electrostatic spinning precursor solution, ultrasonically stirring uniformly, performing electrostatic spinning, drying, and finally calcining in a muffle furnace in an air atmosphere. The product has high lithium ion conductivity (gt; 10 <-3 > S cm <-1 >), and the electrochemical performance and cycling stability of the silicon-based electrode material can be effectively improved due to the high-entropy characteristic. The preparation method disclosed by the invention is simple to operate and relatively low in cost, and a new idea is provided for preparation of the silicon-based composite electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of negative electrode materials for lithium ion batteries, and specifically relates to a high entropy alloy oxide / nano silicon composite negative electrode material for lithium ion batteries and a preparation method thereof. Background Art

[0002] Lithium-ion batteries (LIBs) play a vital role in electronic communication products, energy storage power stations, and electric vehicles (EVs). Electrode materials, as core components, have been proposed as key factors in the design of LIB products, and great consideration has been given to their performance improvement. However, there are still huge challenges in developing electrode materials with excellent performance, especially negative electrode materials. Traditional graphite negative electrode materials have the characteristics of low lithium insertion voltage platform and good cycle stability. Their theoretical specific capacity is 372mAh / g. However, their low specific capacity can no longer meet the needs of today's market. Compared with traditional graphite negative electrodes, silicon (Si), as an alloy-type negative electrode material, has a specific capacity of 3579mAh / g, which is significantly higher than commercial graphite. In addition, silicon negative electrode materials have a lower voltage platform (≈0.4V vs Li / Li + ), abundant reserves and low cost, suitable for meeting the demand for next-generation high-energy-density lithium-ion batteries in electric vehicle applications. Therefore, the development of silicon-based anode materials with excellent performance is key.

[0003] High entropy alloy oxide (HEO) refers to a single-phase oxide obtained by solid dissolving five or more elements in the same sublattice at a molar ratio of 5%-35%. The increase in the mixed configuration entropy caused by the increase in the constituent elements is sufficient to overcome the formation enthalpy of the single-phase compound, thereby preventing the formation of harmful intermetallic compounds. The lithium ion conductivity of HEO is greater than 10 -3 S cm -1 In addition, the high entropy property can effectively improve the cycle stability of electrode materials. At the same time, most transition metal high entropy oxides have high theoretical specific capacity (>1000mAh g -1 ). Based on these advantages, HEO is expected to become an electrode material with good lithium storage performance.

[0004] The combination of Si and transition metal (TM) elements can significantly improve its mechanical properties, which is crucial for the fabrication of crack-free Si-based anodes. For example, by alloying Si with Mn in a 1:1 molar ratio, the Young's modulus can be increased from 150 GPa for Si to 340 GPa for MnSi. Other Si-based alloy anodes such as Fe-Si, Cu-Si, and Ni-Si systems also show improved cycling stability. In order to further improve the performance, it is necessary to improve the overall mechanical properties during the cycle, and it is important to avoid the degradation of mechanical properties during the cycle. Summary of the invention

[0005] In view of the deficiencies in the prior art, the invention aims to provide a high entropy alloy oxide / nano-silicon composite lithium-ion battery negative electrode material and a preparation method thereof. The high entropy alloy oxide / nano-silicon composite lithium-ion battery negative electrode material is a spinel structure, has excellent electrochemical performance and cycle stability, and has a simple preparation method.

[0006] In order to achieve the above object, the present invention adopts the following technical scheme:

[0007] A high entropy alloy oxide / nano silicon composite lithium ion battery negative electrode material, the chemical formula of the lithium ion battery negative electrode material is (FeCoNiCrMn) 3 O 4 / Si, which has a spinel structure; it is prepared from iron salt, nickel salt, cobalt salt, chromium salt, manganese salt and modified nano-silicon, wherein the iron salt, nickel salt, cobalt salt, chromium salt and manganese salt are one or more of nitrates, acetates, acetylacetonates, carbonates, bicarbonates, hydrochlorides and sulfates of metal elements, and the modified nano-silicon is prepared by modifying nano-silicon particles by soaking in citric acid solution, PVP solution or hydrogen peroxide solution.

[0008] The above-mentioned method for preparing a high entropy alloy oxide / nano-silicon composite lithium-ion battery negative electrode material comprises the following steps:

[0009] (1) Mix nano-silicon particles, modified substances and water, stir and centrifuge to obtain modified nano-silicon. Dissolve the electrospinning polymer in a solvent and mix thoroughly to form an electrospinning solution. Then add appropriate amounts of iron salt, nickel salt, cobalt salt, chromium salt, manganese salt and modified nano-silicon in sequence, ultrasonicate for 10-60 minutes, and stir for 12-36 hours to obtain a precursor product 1;

[0010] (2) Using a syringe to absorb the precursor product 1, and then placing the syringe in an electrospinning machine for electrospinning, collecting the electrospinning product, and drying it at 80-120° C. for 8-12 hours to obtain a precursor product 2.

[0011] (3) placing the precursor product 2 in a muffle furnace, first heating it to 100-500° C. for pre-calcination for 0.5-3 h in an air atmosphere, then calcining it at 700-950° C. for 1-12 h, and then naturally cooling it to room temperature to obtain the product (FeCoNiCrMn) 3 O 4 / Si.

[0012] Furthermore, in step (1), the electrospinning solution is prepared from a polymer and a solvent, the polymer is one or more of polyacrylonitrile (PAN) with an average molecular weight of 150,000, polyvinylpyrrolidone (PVP) with an average molecular weight of 1,300,000, and polyvinylidene fluoride (PVDF) with an average molecular weight of 400,000, and the solvent is one or more of deionized water, ethanol, and N,N-dimethylformamide (DMF).

[0013] Furthermore, in step (1), the electrospinning solution is prepared by mixing the polymer and the solvent in a mass ratio of 0.08-0.1:1. The specific process is as follows: first weigh 10 g of the solvent and spin at 200-400 r min -1 Slowly add 0.8-1g polymer under magnetic stirring, stir for 10-30min, then increase the speed to 800-1000r min -1 The mixture was stirred for 12-24 hours to obtain an electrospinning solution.

[0014] Furthermore, in step (1), the iron salt, nickel salt, cobalt salt, chromium salt, or manganese salt is one or more of nitrate, acetate, acetylacetonate, carbonate, bicarbonate, hydrochloride, and sulfate of the corresponding metal element.

[0015] Furthermore, in step (1), the molar ratio of the added iron salt, nickel salt, cobalt salt, chromium salt and manganese salt is 1:1:1:1:1, and the molar ratio of the total molar amount of the iron salt, nickel salt, cobalt salt, chromium salt and manganese salt to the added amount of modified nano-silicon is 1:(0.1-5), wherein the molar amount of modified nano-silicon is calculated based on the molar amount of nano-silicon particles, that is, the weighed amount of modified nano-silicon / molar mass of silicon.

[0016] Furthermore, in step (1), the modified nano-silicon is obtained by modifying nano-silicon particles with citric acid, PVP or hydrogen peroxide. The specific process is: dissolving the modified substance in deionized water, weighing nano-silicon particles (10-100 nm) and dispersing them in the solution, stirring for 12-24 hours, and rotating at 8000 r min. -1 The mixture is centrifuged for 3-10 min, and the precipitate obtained by centrifugation is taken and vacuum dried at 80-100° C. for 12-24 h to obtain modified nano-silicon, wherein the modified substance: deionized water: nano-silicon particles = 1-2 g: 100 mL: 0.1-0.2 g.

[0017] Furthermore, in step (2), the syringe draws 10 mL of the precursor product 1; the process parameters of the electrospinning are: voltage 1-20 kV, ejection speed 0.5-2 mL / h, distance between the syringe needle and the collector 10-20 cm, and inner diameter of the syringe needle 0.61-1.2 mm.

[0018] Furthermore, in step (3), the heating rate of the pre-sintering and calcining is 1-20°C / min.

[0019] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0020] 1. The preparation method of the present invention first prepares a large number of HEO / Si composite fiber lines with micro-nano fiber structures by electrospinning. Since the synthesis is completed in the air in the muffle furnace, the organic matter in the precursor product is oxidized and exhausted, so that a large number of pores are formed in the final product, which to a certain extent alleviates the volume strain of the electrode material during the cycle.

[0021] 2. The introduction of high entropy alloy oxides can not only utilize their excellent high entropy stability to improve the mechanical properties of composite materials and alleviate the cycle stability of electrode materials, but also have excellent lithium ion conductivity and theoretical specific capacity. The combination of HEO and nano-Si effectively improves the performance of electrode materials.

[0022] 3. In the present invention, by modifying the nano-silicon particles, the negative charge density on the surface of the nano-silicon can be increased. Under the action of electrostatic force, a large amount of metal ions are wrapped on the nano-silicon particles, and after calcination, a core-shell structure (FeCoNiCrMn) of the nano-silicon wrapped by an oxide alloy shell can be formed. 3 O 4 / Si(such as Figure 3 As shown, the right figure is an enlarged view of the red dotted box area in the left figure, where the particles have a black outer circle as the HEO shell and a light inner area as Si), which prevents direct contact between silicon and the electrolyte and improves the cycle stability of the electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The SEM morphology of the high entropy alloy oxide / nano-silicon composite lithium-ion battery negative electrode material prepared in Comparative Example 1(a) and Example 1(b);

[0024] Figure 2 This is the SEM morphology of the precursor product 2 in Example 1;

[0025] Figure 3 TEM morphology of the high entropy alloy oxide / nano-silicon composite lithium-ion battery negative electrode material prepared in Example 1;

[0026] Figure 4 The XRD patterns of the products prepared in Example 1, Example 2 and Comparative Example 1 are as follows; it can be seen that Comparative Example 1 shows a peak of a single-phase cubic spinel (PDF#22-1084) with a Fd-3m space group, and a spinel structure (FeCoNiCrMn) is synthesized. 3 O 4; In Examples 1 and 2, single-phase cubic spinel (PDF#22-1084) and Si (PDF#97-004-1979) peaks can be seen, indicating that (FeCoNiCrMn) 3 O 4 and Si;

[0027] Figure 5 The half-cell prepared with the high entropy alloy oxide / nano-silicon composite lithium-ion battery negative electrode material prepared in Example 1 as raw material and the half-cell prepared with the product of Comparative Example 1 as raw material at 0.1A g -1 The following cycle performance comparison chart;

[0028] Figure 6 The half-cell prepared with the high entropy alloy oxide / nano-silicon composite lithium-ion battery negative electrode material prepared in Example 1 as raw material and the half-cell prepared with the product of Comparative Example 1 as raw material at 1.0 A g -1 The following cycle performance comparison chart. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is described in detail below through specific embodiments and drawings, but the implementation methods of the present invention are not limited thereto.

[0030] Silicon nanoparticles (particle size range: 60-90 nm), iron nitrate nonahydrate (Fe(NO3)3·9H2O, purity 99%), cobalt nitrate hexahydrate (Co(NO3)2·6H2O, purity 99%), nickel nitrate hexahydrate (Ni(NO3)2·6H2O, purity 99%), chromium nitrate nonahydrate (Cr(NO3)3·9H2O, purity 99%), manganese nitrate hexahydrate (Mn(NO3)2·6H2O, purity 99%), N,N-dimethylformamide (DMF), and polyacrylonitrile (PAN, molecular weight ≥150000). All of the above reagents were of analytical grade and purchased directly from Shanghai Aladdin Biochemical Technology Co., Ltd. and used directly in this experiment without any further purification.

[0031] Embodiment 1 A method for preparing a high entropy alloy oxide / nano-silicon composite lithium-ion battery negative electrode material comprises the following steps:

[0032] Preparation of modified nano-silicon: 1.5 g of citric acid was dissolved in 100 mL of deionized water, and 0.1 g of nano-silicon particles (60-90 nm) were dispersed in the above solution, stirred for 24 h, and heated at 8000 r min. -1 The mixture was centrifuged for 5 min, and the precipitate obtained by centrifugation was vacuum dried at 80 °C for 12 h to obtain citric acid-modified nano-silicon;

[0033] Preparation of electrospinning solution: Using N,N-dimethylformamide (DMF) as solvent, weigh 10 g of DMF at room temperature (25 °C) and spin at 400 r min -1 Slowly add 1g of polymer PAN with an average molecular weight of 150,000 under magnetic stirring, stir for 10 minutes, and then increase the speed to 1000 r min. -1 Stir at high speed for 24 h to obtain PAN electrospinning solution;

[0034] 0.5 mmol of ferric nitrate nonahydrate, 0.5 mmol of nickel nitrate hexahydrate, 0.5 mmol of cobalt nitrate hexahydrate, 0.5 mmol of chromium nitrate nonahydrate, 0.5 mmol of manganese nitrate hexahydrate and 0.075 g of citric acid-modified nano-silicon (calculated based on the molar mass of silicon, i.e. 0.075 g / 28 g / mol = 2.68 mmol, the same below) were sequentially added to the PAN electrospinning solution, ultrasonicated for 30 min, stirred for 12 h, and the precursor product 1 was obtained;

[0035] Use a syringe with a needle inner diameter of 0.84 mm to draw 10 mL of the precursor product 1; then place it in an electrospinning machine, the electrospinning voltage is 20 kV, the ejection speed is set to 1 mL / h, the distance between the syringe needle and the collector is 15 cm, the ambient temperature is controlled to be 25±2°C, the relative humidity is 20%, and the spinning is continued for 10 hours. After collecting the electrospinning product, it is dried at 80°C for 12 hours to obtain the precursor product 2;

[0036] The precursor product 2 is placed in a muffle furnace, heated to 200°C at a heating rate of 5°C / min under air atmosphere for pre-calcination for 1h, then heated to 800°C at a heating rate of 5°C / min for calcination for 1h, and then naturally cooled to room temperature to obtain the high entropy alloy oxide / nano-silicon composite lithium ion battery negative electrode material (FeCoNiCrMn) 3 O 4 / Si.

[0037] Embodiment 2 A method for preparing a high entropy alloy oxide / nano-silicon composite lithium-ion battery negative electrode material comprises the following steps:

[0038] Preparation of modified nano-silicon: 3 g of citric acid was dissolved in 200 mL of deionized water, and 0.2 g of nano-silicon particles (60-90 nm) were dispersed in the solution, stirred for 24 h, and heated at 8000 r min. -1 The mixture was centrifuged for 5 min, and the precipitate obtained by centrifugation was vacuum dried at 80°C for 24 h to obtain citric acid-modified nano-silicon;

[0039] Preparation of electrospinning solution: N, N-dimethylformamide (DMF) was used as solvent. 10 g of DMF was weighed and stirred at 400 r min at room temperature. -1Slowly add 1g of polymer PAN with an average molecular weight of 150,000 under magnetic stirring, stir for 10 minutes, and then increase the speed to 1000 r min. -1 Stir at high speed for 12 h to obtain PAN electrospinning solution;

[0040] 0.5 mmol of ferric nitrate nonahydrate, 0.5 mmol of nickel nitrate hexahydrate, 0.5 mmol of cobalt nitrate hexahydrate, 0.5 mmol of chromium nitrate nonahydrate, 0.5 mmol of manganese nitrate hexahydrate and 0.15 g of nano-silicon modified with citric acid were added to the PAN electrospinning solution in sequence, ultrasonicated for 30 min, stirred for 12 h, and the precursor product 1 was obtained;

[0041] Use a syringe with a needle inner diameter of 0.84 mm to draw 10 mL of the precursor product 1; then place it in an electrospinning machine, the electrospinning voltage is 20 kV, the ejection speed is set to 1 mL / h, the distance between the syringe needle and the collector is 15 cm, the ambient temperature is controlled to be 25±2°C, the relative humidity is 20%, and the spinning is continued for 10 hours. After collecting the electrospinning product, it is dried at 80°C for 12 hours to obtain the precursor product 2;

[0042] The precursor product 2 is placed in a muffle furnace, heated to 200°C at a heating rate of 5°C / min under air atmosphere conditions and pre-fired for 1 hour, then heated to 800°C at a heating rate of 5°C / min and calcined for 1 hour, and then naturally cooled to room temperature to obtain the high entropy alloy oxide / nano-silicon composite lithium-ion battery negative electrode material.

[0043] Embodiment 3 A method for preparing a high entropy alloy oxide / nano-silicon composite lithium-ion battery negative electrode material comprises the following steps:

[0044] Preparation of modified nano-silicon: 1.5 g of citric acid was dissolved in 100 mL of deionized water, and 0.1 g of nano-silicon particles (60-90 nm) were dispersed in the solution, stirred for 24 h, and heated at 8000 r min. -1 The mixture was centrifuged for 5 min, and the precipitate obtained by centrifugation was vacuum dried at 80 °C for 18 h to obtain citric acid-modified nano-silicon;

[0045] Preparation of electrospinning solution: N, N-dimethylformamide (DMF) and anhydrous ethanol were used as solvents. At room temperature, 6 g of DMF and 4 g of anhydrous ethanol were weighed and mixed. -1 Slowly add 1 g of polyvinyl pyrrolidone (PVP) with an average molecular weight of 1,300,000 under magnetic stirring, stir for 10 min, and then increase the speed to 1,000 r min. -1 Stir at high speed for 18 h to obtain PVP electrospinning solution;

[0046] 0.5 mmol of ferric nitrate nonahydrate, 0.5 mmol of nickel nitrate hexahydrate, 0.5 mmol of cobalt nitrate hexahydrate, 0.5 mmol of chromium nitrate nonahydrate, 0.5 mmol of manganese nitrate hexahydrate and 0.075 g of nano-silicon modified with citric acid were added to the PVP electrospinning solution in sequence, ultrasonicated for 30 min, stirred for 12 h, and the precursor product 1 was obtained;

[0047] Use a syringe with a needle inner diameter of 0.84 mm to draw 10 mL of the precursor product 1; then place it in an electrospinning machine, the electrospinning voltage is 20 kV, the ejection speed is set to 1 mL / h, the distance between the syringe needle and the collector is 15 cm, the ambient temperature is controlled to be 25±2°C, the relative humidity is 20%, and the spinning is continued for 10 hours. After collecting the electrospinning product, it is dried at 80°C for 12 hours to obtain the precursor product 2;

[0048] The precursor product 2 is placed in a muffle furnace, heated to 200°C at a heating rate of 5°C / min under air atmosphere conditions and pre-fired for 1 hour, then heated to 800°C at a heating rate of 5°C / min and calcined for 1 hour, and then naturally cooled to room temperature to obtain the high entropy alloy oxide / nano-silicon composite lithium-ion battery negative electrode material.

[0049] Comparative Example 1 A method for preparing a negative electrode material for a high entropy alloy oxide lithium ion battery comprises the following steps:

[0050] Take N,N-dimethylformamide (DMF) as solvent, weigh 10g DMF solvent, and heat at 400r min -1 Slowly add 1g of polymer PAN with an average molecular weight of 150,000 under magnetic stirring, stir for 10 minutes, and then increase the speed to 1000 rmin. -1 Stir at high speed for 24 h to obtain PAN electrospinning solution;

[0051] 0.5 mmol of ferric nitrate nonahydrate, 0.5 mmol of nickel nitrate hexahydrate, 0.5 mmol of cobalt nitrate hexahydrate, 0.5 mmol of chromium nitrate nonahydrate, and 0.5 mmol of manganese nitrate hexahydrate were added to the PAN electrospinning solution in sequence, ultrasonicated for 30 min, and stirred for 12 h to obtain precursor product 1;

[0052] Use a syringe with a needle inner diameter of 0.84 mm to draw 10 mL of the precursor product 1, and then place it in an electrospinning machine. The electrospinning voltage is 20 kV, the ejection speed is set to 1 mL / h, the distance between the syringe needle and the collector is 15 cm, the ambient temperature is controlled to be 25±2°C, the relative humidity is 20%, and the spinning is continued for 10 hours. After collecting the electrospinning product, it is dried at 80°C for 12 hours to obtain the precursor product 2;

[0053] The precursor product 2 is placed in a muffle furnace and pre-fired at 200°C at a heating rate of 5°C / min for 1 hour under air atmosphere conditions, then heated to 800°C at a heating rate of 5°C / min and calcined for 1 hour, and then naturally cooled to room temperature to obtain the high entropy alloy oxide lithium ion battery negative electrode material.

[0054] Electrochemical performance test

[0055] The negative electrode materials of lithium-ion batteries obtained in Examples 1-3 and Comparative Example 1 were respectively made into half-cells for electrochemical performance measurement. The assembly methods of the half-cells were as follows: the sample to be tested, the conductive agent (Super P), and the binder (sodium alginate) were mixed in a mass ratio of 7:2:1, and mixed and ground evenly with deionized water as the solvent. The prepared electrode slurry was evenly coated on a 3cm×10cm copper foil, vacuum dried at 60℃ for 12h, and then taken out and punched into a pole piece with a diameter of 12mm. The active material loading was between 0.8 and 1.2mg / cm 2 The half-cell was assembled in a glove box (water and oxygen content were both less than 0.01 ppm) using a CR2032 button cell. The separator used was made of Celgard 2400 polypropylene separator, and the CR2032 button cell used a commercially available round lithium sheet with a diameter of 1.5 cm as the counter electrode. The electrolyte was 1M LiPF 6 The mixed solution is composed of ethylene carbonate (EC) and diethyl carbonate (DEC) (the volume ratio of EC to DEC is 1:1). The electrochemical charge and discharge performance is evaluated using a Blue Power CT2001A battery test system (Wuhan Blue Power Electronics Co., Ltd.).

[0056] like Figure 1 As shown, Figure 1 (a) is comparative example 1, Figure 1 (b) is a SEM morphology of the negative electrode material of the lithium-ion battery prepared in Example 1. It can be seen that in Comparative Example 1, there is no nano-silicon composite, the HEO fiber particles are relatively uniform, and no porous structure is shown; in Example 1, the fiber line presents an obvious porous structure, and the surface is uniformly distributed particles. Figure 3 The TEM morphology of the high entropy alloy oxide / nano-silicon composite lithium-ion battery negative electrode material prepared in Example 1 is shown. The fiber line presents a porous structure, the nano-silicon particles are evenly distributed therein, and a core-shell structure formed by HEO-coated nano-silicon can be observed.

[0057] like Figure 5 , 6 The results are as follows: a half-cell made of the high entropy alloy oxide / nano-silicon composite lithium-ion battery negative electrode material prepared in Example 1 as a raw material and a half-cell made of the high entropy alloy oxide lithium-ion battery negative electrode material prepared in Comparative Example 1 as a raw material at 0.1A g-1 , 1.0A g -1 The cycle performance diagram below. Figure 5 In the comparison between Example 1 and Comparative Example 1, at 0.1A g -1 The initial discharge capacities at the current density were 1230mAh / g and 1211mAh / g, respectively, and the residual capacities after 150 cycles were 1237mAh / g and 792mAh / g, respectively. Figure 6 In the high rate performance test, at 1.0A g -1 Under the current density, the half-cell made of the high entropy alloy oxide / nano-silicon composite lithium-ion battery negative electrode material prepared in Example 1 as raw material has a residual capacity of 679 mAh / g after 500 cycles, and the half-cell made of the high entropy alloy oxide lithium-ion battery negative electrode material prepared in Comparative Example 1 as raw material has a residual capacity of 342 mAh / g after 200 cycles. It can be seen that the addition of modified nano-silicon can greatly improve the electrochemical properties of HEO, and the half-cell made of the high entropy alloy oxide / nano-silicon composite lithium-ion battery negative electrode material prepared in Example 1 as raw material has excellent specific capacity and cycle stability.

Claims

1. A method for preparing a high entropy alloy oxide / nano-silicon composite lithium-ion battery negative electrode material, the preparation method comprising the following steps: (1) Mixing nano-silicon particles, a modified substance and water, stirring and centrifugally drying to obtain modified nano-silicon; The electrospinning polymer is dissolved in a solvent and mixed thoroughly to form an electrospinning solution, and then appropriate amounts of iron salt, nickel salt, cobalt salt, chromium salt, manganese salt and modified nano-silicon are added thereto in sequence, ultrasonicated for 10-60 minutes, and stirred for 12-36 hours to obtain a precursor product 1; (2) using a syringe to absorb the precursor product 1, and then placing the syringe in an electrospinning machine for electrospinning, collecting the electrospinning product, and drying it at 80-120° C. for 8-12 hours to obtain the precursor product 2; (3) The precursor product 2 is placed in a muffle furnace, and in an air atmosphere, the temperature is first raised to 100-500° C. for pre-calcination for 0.5-3 h, and then calcined at 700-950° C. for 1-12 h, and then naturally cooled to room temperature to obtain the product (FeCoNiCrMn)3O4 / Si.

2. The preparation method according to claim 1, characterized in that: In step (1), the electrospinning solution is prepared from a polymer and a solvent, wherein the polymer is one or more of polyacrylonitrile (PAN) with an average molecular weight of 150,000, polyvinylpyrrolidone (PVP) with an average molecular weight of 1,300,000, and polyvinylidene fluoride (PVDF) with an average molecular weight of 400,000, and the solvent is one or more of deionized water, ethanol, and N,N-dimethylformamide (DMF).

3. The preparation method according to claim 2, characterized in that: In step (1), the electrospinning solution is prepared by mixing the polymer and the solvent in a mass ratio of 0.08-0.1:

1. The specific process is as follows: first weigh the solvent and spin at 200-400 r min -1 Slowly add the polymer under magnetic stirring, stir for 10-30 minutes, then increase the speed to 800-1000 r min -1 The mixture was stirred for 12-24 hours to obtain an electrospinning solution.

4. The preparation method according to claim 1, characterized in that: In step (1), the iron salt, nickel salt, cobalt salt, chromium salt and manganese salt are one or more of nitrates, acetates, acetylacetonates, carbonates, bicarbonates, hydrochlorides and sulfates of the corresponding metal elements.

5. The preparation method according to claim 4, characterized in that: In step (1), the molar ratio of the added iron salt, nickel salt, cobalt salt, chromium salt and manganese salt is 1:1:1:1:1, and the molar ratio of the total molar amount of the iron salt, nickel salt, cobalt salt, chromium salt and manganese salt to the added amount of modified nano-silicon is 1:(0.1-5).

6. The preparation method according to claim 1, characterized in that: In step (1), the modified nano-silicon is obtained by modifying nano-silicon particles with citric acid, PVP or hydrogen peroxide. The specific process is: dissolving the modified substance in deionized water, weighing the nano-silicon particles and dispersing them in the solution, stirring for 12-24 hours, and rotating at 8000 r min. -1 Centrifuge for 3-10 min, take the precipitate obtained by centrifugation, and vacuum dry it at 80-100 °C for 12-24 h to obtain modified nano-silicon, wherein the modified substance: deionized water: nano-silicon particles = 1-2 g: 100 mL: 0.1-0.2 g.

7. The preparation method according to claim 1, characterized in that: In step (2), the process parameters of the electrospinning are: voltage 1-20 kV, ejection speed 0.5-2 mL / h, distance between the syringe needle and the collector 10-20 cm, and inner diameter of the syringe needle 0.61-1.2 mm.

8. The preparation method according to claim 1, characterized in that: In step (3), the heating rates of the pre-sintering and calcining are both 1-20°C / min.

9. The high entropy alloy oxide / nano silicon composite lithium ion battery negative electrode material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The chemical formula of the obtained high entropy alloy oxide / nano-silicon composite lithium-ion battery negative electrode material is (FeCoNiCrMn)3O4 / Si, which is a spinel structure, forming a core-shell structure in which the oxide alloy shell wraps the nano-silicon.

Citation Information

Patent Citations

  • A high-performance silicon negative electrode active material and a preparation method thereof

    CN108963229A

  • High-specific-energy battery preparation method and high-specific-energy battery

    CN117747967A

  • High-entropy alloy oxide lithium ion battery negative electrode material and preparation method thereof

    CN118206124A

  • Preparation method and application of high-entropy alloy and carbon fiber composite nanomaterial

    CN118389966A

  • High-entropy alloy nano-particle loaded carbon fiber cathode catalyst, preparation method and application of high-entropy alloy nano-particle loaded carbon fiber cathode catalyst in all-solid-state high-low-temperature zinc air battery

    CN118448654A